The impact of opioid analgesics on the gastrointestinal tract function and the current management possibilities [Polish version: Wpływ opioidowych środków przeciwbólowych na czynność układu pokarmowego oraz aktualne możliwości postępowania terapeutycznego p. 132] - Leppert, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2012)
Opioid-induced bowel dysfunction (OIBD) comprises gastrointestinal symptoms such as constipation, anorexia, nausea, vomiting, gastro-oesophageal reflux, delayed digestion, abdominal pain, bloating, hard stool and incomplete evacuation that significantly deteriorate patients’ quality of life and compliance. Approximately one third of patients treated with opioids do not adhere to the opioid regimen or simply quit the treatment due to OIBD. Several strategies are undertaken to prevent or treat OIBD. Traditional oral laxatives are used but their effectiveness is limited and they display adverse effects. Other possibilities comprise opioid switch or changing the administration route. New therapies target opioid receptors in the gut that seem to be the main source of OIBD. One is a combination of an opioid and opioid antagonist (oxycodone/naloxone) in prolonged-release tablets, and another is a purely peripherally acting opioid receptor antagonist (methylnaltrexone) available in subcutaneous injections. The aim of this article is to review the pathomechanism and possible treatment strategies of OIBD.